Pengaruh Corporate Social Responsibility (CSR) Terhadap Kinerja Bank Pembangunan Daerah (BPD) Lampung Melalui Reputasi Sebagai Variabel Mediasi - Sani, Faiz Ardana; Erlina, RR.; Husna, Nurul (CV. ITTC INDONESIA, 2025)
The banking industry in Indonesia is facing reputation-related challenges, which have contributed to declining customer trust and reduced third-party funds. This raises concerns regarding the effectiveness of Corporate Social Responsibility (CSR) programs in enhancing a bank’s reputation and performance This study aims to examine the effect of CSR on the performance of Bank Pembangunan Daerah (BPD) Lampung and to assess the mediating role of reputation in this relationship. The research adopts a quantitative approach, using primary data collected from 61 decision-makers at BPD Lampung through questionnaireand analyzed using Structural Equation Modeling (SEM) via Smart PLS to test both direct and indirect effects between variables. The results show that CSR has a positive and significant impact on company performance. Additionally, corporate reputation significantly mediates the relationship between CSR and performance, indicating that reputation is a crucial factor in amplifying the benefits of CSR. These findings reinforce the relevance of the Resource-Based View and Stakeholder Theory in developing sustainable competitive advantage through corporate social responsibility and reputation management. Furthermore, BPD Lampung is advised to focus on initiatives that enhance operational efficiency, including an evaluation of the security level of the banking system and asset profitability.